Analysis of the Potential for Savings in Electrical Energy Consumption in Lifts: Case Study in Indonesia - Deni Almanda; Anwar Ilmar Ramadhan (Journal of Applied Sciences and Advanced Technology, 2020)
Regenerative Drive is a motor drive system in an elevator that can also generate electrical energy while consuming electrical energy in the elevator machine, Regenerative Drive converts gravitational potential energy into electrical energy by utilizing the operating characteristics of the lift and the weight difference between the lift cage and the load balancing (Counterweight). ). The resulting regenerative power is recovered by returning to the building electricity and being used in other electrical equipment. Regenerative drive lift test location is located in Building which has an elevator using Regenerative Drive. With a motor power of 38.6 kW and can produce regenerative power of 29 kW.